Virtual Reality-Based Anatomy Learning: A Sustainable Alternative to Cadaveric Dissection in Medical Education - Hasti, Novrini; Sitanggang , Andri Sahata; Syafariani, R Fenny; Sari, Febilita Wulan; Pangaribuan, Imelda; Wahyuni, Wahyuni; Radliya, Nizar Rabbi; Susanti, Sussy; Gradiansyah, Aqbil (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
This quasi-experimental study aimed to compare the effectiveness, cost-benefit, and long-term knowledge retention of VR-based anatomy instruction versus traditional cadaveric dissection. We randomized 300 preclinical medical students to VR (n=150) or cadaveric instruction (n=150). Validated knowledge tests, engagement scales, and cost metrics were administered immediately post-intervention and at 3- and 6-month follow-ups. VR yielded higher immediate post-test scores (78.6 ± 9.2 vs 74.3 ± 8.7; p<0.001; d=0.48) and better 6-month retention (72.1 ± 9.7 vs 65.4 ± 10.2; p<0.001; d=0.67). Student engagement was greater with VR (4.2 ± 0.6 vs 3.7 ± 0.7; p<0.001). Per-student costs were 58% lower (US206.6 vs US491.7), delivering an 81.8% 5-year ROI. These results suggest that VR’s immersive 3D visualization, standardization, and repeatable practice enhance cognitive encoding and reduce logistical and safety burdens, contributing to superior learning and retention. In conclusion, VR outperformed cadaver-based teaching on learning outcomes, retention, engagement, and cost-effectiveness, supporting its adoption as a sustainable alternative in medical education.